(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The growing demand for English language proficiency in academic and professional settings has necessitated the adoption of innovative teaching methodologies that cater to the diverse needs of learners. Among these, the integrative approach has gained prominence for its ability to combine multiple language skills— listening, reading, writing, and speaking—into a cohesive and dynamic learning experience. This approach aligns with the principles of communicative language teaching (CLT), which emphasizes real-life communication, learner-centered instruction, and the development of practical language competencies[1]. For university students, who often require English not only for academic success but also for future career opportunities, the integrative approach offers a practical and effective framework that bridges the gap between classroom learning and real-world application.